2D Metal Chalcogenide Nanopatterns by Block Copolymer Lithography. (16th October 2018) - Yun, Taeyeong; Jin, Hyeong Min; Kim, Dong‐Ha; Han, Kyu Hyo; Yang, Geon Gug; Lee, Gil Yong; Lee, Gang San; Choi, Jin Young; Kim, Il‐Doo; Kim, Sang Ouk
Abstract: Nanoscale structure engineering is in high demand for various applications of 2D transition metal dichalcogenides (TMDs). An edge‐exposed 2D polycrystalline MoS2 nanomesh thin film is demonstrated via block copolymer (BCP) nanopatterning. Molybdenum nanomesh structure is formed by direct metal deposition of hexagonal cylinder BCP nanotemplate and the following lift‐off process. Subsequent sulfurization of the molybdenum nanomesh creates MoS2 nanomesh thin films without any degradative etching step. The approach is applicable to not only other metal sulfides and oxides but also other nanoscale structures of TMD thin films including nanodot and nanowire array by means of various BCP nanotemplate shapes. As the edge site of MoS2 is highly active for NO2 sensing, the edge‐exposed MoS2 nanomesh demonstrates sevenfold enhancement of sensitivity for NO2 molecules compared to uniform thin film as well as superior reversibility even under 80% relative humidity environment. This structure engineering method could greatly strengthen the potential application of 2D TMD materials with the optimal customized nanoscale structures. Abstract : Nanopatterning of transition metal dichalcogenides (TMD) is presented. By exploiting block copolymer nanotemplate, desired metal nanopattern, including nanomesh, nanodot, and nanowire arrays, can be readily obtained with large area. The post sulfurization process gives rise to nanopattered TMD. The edge‐exposed MoS2 nanomesh exhibits a sevenfold enhancement of sensitivity for NO2 sensing and superior reversibility compared to the uniform thin film.